Wellbeing wins for teachers : what we can learn from iconic individuals - Leese, Tracey; Rowley, Charlotte; Brown, Lauren (New York, NY : Routledge, 2024)
"This exciting and inspiring text offers easy-to-implement strategies and tools to improve teacher wellbeing in schools. Teacher wellbeing is of paramount importance in the profession and has never been as necessary as it is today, even being included at the heart of the current Ofsted framework. Drawing together theory, popular culture and real-life stories from teachers, each chapter focuses on one of 10 inspirational and iconic individuals from diverse backgrounds as archetypes to explore key strands of wellbeing including healthy habits, resourcefulness, resilience, managing pressure, workload, time management, and positivity. Emphasising the importance of wellbeing and aspiration for teachers at all stages of their career, the chapters feature: a constructed definition of each icon and how their achievements translate into the teaching profession, a case study exploring how a teacher has overcome wellbeing challenges in their career and how this shaped them as a professional, key lessons and takeaway actions Including a Foreword by Hannah Wilson, Co-founder and Director of Diverse Educators, Wellbeing Wins for Teachers translates the abstract notion of wellbeing into tangible and practical strategies for all teachers"--
Chapter 1: Let them eat cake -- Chapter 2: Winning at well-being -- Chapter 3: Well-being win 1: Beyoncé and healthy habits -- Chapter 4: Well-being win 2: Robbie Williams and resourcefulness -- Chapter 5: Well-being win 3: Dame Kelly Holmes and resilience -- Chapter 6: Well-being win 4: Stephen Hawking and pressure -- Chapter 7: Well-being win 5: Taylor Swift and workload -- Chapter 8: Well-being win 6: Marcus Rashford and compassion -- Chapter 9: Well-being win 7: Dolly Parton and time management -- Chapter 10: Wellbeing win 8: Joe Wicks and positivity -- Chapter 11: Well-being win 9: Tina Turner and self-awareness -- Chapter 12: Well-being win 10: Tom Daly and creativity.
Keywords: Teachers -- Mental health; Teaching -- Psychological aspects; Teachers -- Job stress; Teacher morale; Well-being.; EDUCATION / Secondary; EDUCATION / Elementary; EDUCATION / Professional Development